From social contradiction to social competition as the basic legal regime (mode) of statehood (Part II) - A. V. Butakov (Правоприменение, 2024)
The subject of the article is social competition as the basic legal regime (mode) of statehood as a systemic channel that determines the functioning of property as a goal and the state as a means.The aim of the article is to confirm or refute hypothesis that the resolution of social contradictions is a kind of legal regime for the realization of property as the fundamental purpose of the existence of the state.According to the author's methodology of normative structuralism, the assignment to each mode of property organization of a specific function (social development function, social compromise (convergence) function, social security function) generated the corresponding potential for the emergence and existence of social contradictions, where the state as an artificial (reasonable) sufficiency had to direct the energy of the said contradictions into the normative-legal channel and thus ensure the existence of social competition.The main results. The restriction and leveling of social competition and the transition to domination as the basic legal regime (mode) of statehood destroys the natural mechanism for resolving social contradictions and transfers this mechanism to the plane of directive political and ideological expediency. As a result, the power of the structural organization of the state is transformed into a goal of its existence, and property only into a means of realizing this goal. There is a disavowal of property as a fundamental goal of the existence of the state; the escalation of its imperialization begins, triggering the destruction of social competition as the basic legal regime (mode) of statehood. There is a danger of an existential rupture between the three most important social institutions of human civilization: property, competition, and the state.Society, constituting the creation of the state as artificial (reasonable) sufficiency, through the functioning of the structural organization of power has fixed the fundamental purpose of existence - property in the form of an integral structural platform of the main ways of its organization (private (individualized), mixed (corporate), general (collective)), assigning to each of them the execution of the corresponding social function.Conclusions. Society, realizing the existence of a social contradiction, purposefully forms appropriate ways (rules) to overcome them to ensure its progressive development. The essence of the legal regime as the existence of the resolution of this social contradiction can be defined by the concept of “competition”.